RISK GROUPS AND PROGNOSTICATED SIGNIFICANCE OF RISK STRATIFICATION CRITERIA IN ARTERIAL HYPERTENSION DEVELOPMENT AMONG SCHOOLCHILDREN OF BURYAT REPUBLIC - I. O. Vologdina; A. B. Bimbayev; A. G. Mondodoev (Acta Biomedica Scientifica, 2012)
The prevalence of risk factors for heart diseases was studied in 7-17 years-old. children of two ethnic groups living in the Buryat Republic. It has been established that the combination of two and more risk factors increases the danger of arterial hypertension development. Ethnic component has no any significance in the development of heart abnormalities.